Synthesis and study of the properties of derivatives 4-phenyl-5-(1H-pyrrol-2-yl)-4H-1,2,4-triazole-3-thiols - A. S. Gotsulya; D. P. Verba; O. I. Panasenko; Ye. G. Knysh (The State Expert Center of the Ministry of Health of Ukraine, 2018)
The successful use of drugs, derivatives of 1,2,4-triazole, creates the conditionsfor the production and investigation of properties of new derivatives of this heterocyclic system. The aim of this work was synthesis and study of physical and chemical properties of new derivatives of 1,2,4-triazole-3-thiol containing synthon of pyrrole. The object of the study was a 4-phenyl-5-(pyrrol-2-yl)-1,2,4-triazole-3-ylthio-R-carbothioamides. To achieve this goal it was necessary to solve following tasks: to conduct the selection of the optimum base structure to determine the most efficient way of chemical modification of the precursor of targeted synthesis, to carry out selection of necessary methods of synthesis, to investigate the physico-chemical properties and to set the structure of the obtained compounds. The synthesis of target products of the reaction was carried out using as starting material pyrrole, which with using the form non-catalytic form of reaction of the Fridel-Crafts was transformed into 2,2,2-trichloro-1-(pyrrol-2-yl), ethanol. The resulting material in the result of reaction of hydrazinolysis was converted into the pyrrol-2-carbohydrazide. The obtained intermediate product was used in the reaction of nucleophilic joining of phenylisothiocyanate with subsequent intramolecular alkaline heterocyclization. Synthesized thiol was used in the reaction of alkylation. The structure of the obtained substances are confirmed by using elemental analysis, 1H-NMR-spectroscopy, and their individuality - chromatographic methods of analysis. The resulting substances are an interesting object for further studies, especially biological activity.